Voluntary Disclosure Practices in the Family Business Context: the Case of Listed Family-Controlled Companies in Malaysia - Zaini, Syeliya Md (International Journal of Engineering and Technology, 2018)
The aim of this paper is to analyse the nature and factors that contribute to the voluntary disclosure practice by listed family owned companies. There were 41 stakeholders, consisting preparers and users of voluntary information in the companies’ annual report, were interviewed. This paper reveals that voluntary disclosure reporting practice in the companies’ annual reports have been contextually ingrained in the technical processes of accounting reporting. Analysis from the interviews reveal two driving factors contributing to the amount of additional information disclosed voluntarily by listed family owned firms. The two driving factors are first, managers’ individual family root background, and second the family’s business management setting. This study contributes significantly to the existing literature, particularly on family owned companies. Further, there are few studies investigate the effect of family-controlled ownership on voluntary disclosure practice. Finally, this study was conducted in a developing countries with strong political favouritism and cultural influence.